Intelligent Manipulator with Flexible Link and Joint: Modeling and Vibration Control. (31st January 2020) - Shao, Minqiang; Huang, Yuming; Silberschmidt, Vadim V.
Abstract : This paper presents a finite-element (FE) model of a manipulator with a flexible link and flexible joint as well as embedded PZT actuators and proposes a corrected rebuilt reduced model (CRRM) to make its dynamic characteristics more consistent with reality and facilitate control design. The CRRM considers the holding torque of the manipulator driving motor and eliminates the response divergence induced by a fault of the mass matrix of the FE model. In order to reduce the dimensions and maintain the precision of the model, an iterated improved reduction system (IIRS) method is adopted. Additionally, a LQR controller is designed based on the output function of the improved model. The simulation results demonstrate that the CRRM is consistent with reality and the active controller has good performance in suppressing vibration of the manipulator with both the flexible link and the flexible joint.